Universities as facilitators of sustainable regional development: The role of knowledge, leadership and governance - Sabine Sedlacek (European Regional Science Association (ERSA), 2010)
The question of how universities do stimulate regional economic development is mainly inquired in studies focusing on innovation and entrepreneurship. In these studies universities are seen as important actors within regional innovation systems (RIS). Within these RIS universities fulfill besides their training and education (human capital) function a knowledge production and transfer function. Studies on sustainable regional development are additionally focusing more and more on governance issues and the role of different stakeholders within governance networks and their ability to contribute to a more sustainable development at the regional level. Universities are important governance stakeholders, since their administrators and faculty members are eligible partners for regional governments. Here it is mainly their research capacity which is often used for expertise, e.g. to contribute to regional economic development plans. The role of institutions in fostering sustainable development at the regional level gained, especially in Europe, major importance since multi-level governance (MLG) is the number one concept in the European Union regional policy. The focus on institutional cooperation and how this network cooperation leads to a more effective implementation of sustainable development is the subject of several research agendas focusing on governance for sustainable development. There is a lack of knowledge and expertise with respect to the links between certain institutions and the broader society, and hence their ability to foster sustainable regional development. In this regard universities can serve as facilitators between societal and other institutional actors. In order to fill this gap the question of how the sustainable policy implementation process could be supported by universities acting in partnership with other institutional actors will be addressed. We will introduce an analytical framework which would allow us to test hypotheses extracted out of existing theoretical and empirical literature about universities as key actors in advancing sustainable development. The goal is to filter both factors enhancing sustainable development and obstacles and barriers that are hindering sustainable development.
Keywords: 330; governance for sustainable development; universities; regions